The Conceptual Structure of Arabic Critical Discourse in Light of Cognitive Linguistics: An Applied Study of Abd al-Qahir al-Jurjani's "Dala'il al-I'jaz" (Al-Farooq Journal of Sciences, 2026)
This research seeks to re-read classical Arabic critical and rhetorical heritage through the lens of contemporary cognitive linguistics, taking the book Dala'il al-I'jaz (The Proofs of Inimitability) by Abd al-Qahir al-Jurjani (d. 471 AH) as a practical field of study.The study is built upon a fundamental hypothesis: that al-Jurjani's core propositions—such as takhyil (poetic imagination), the theory of nazm (construction/system), the subtle distinction between "meaning" and the "meaning of meaning," and the consideration of situational context (muqtada al-hal)—carry within their epistemological depths an advanced cognitive intuition. This intuition fundamentally converges with key concepts in cognitive linguistics, including conceptual metaphor, mental spaces, frame theory, and conceptual structure.The study adopts a descriptive-analytical approach to dissect the dimensions of these concepts, tracing their practical applications in selected models from Dala'il. The research concludes that the classical Arabic critical mind was deeply aware of the intimate and profound relationship between cognitive processes and linguistic structure. Consequently, it strongly rejected the fragmentation of language and the arbitrary separation of verbal form from its semantic significance—a stance that directly intersects with the "generalization commitment" advocated by cognitive linguistics today.
Keywords: Cognitive Linguistics, Conceptual Structure, Critical Discourse, Theory of Nazm, Meaning of Meaning, Abd al-Qahir al-Jurjani